Microencapsulación del jugo de mandarina secado por aspersión. - Encalada Aldaz, Jaime Esteban (2022)
The objective of this research was to evaluate the effects of the main factors in the microencapsulation process of mandarin juice to obtain spray-dried powder, as an alternative method of juice preservation. The physical-chemical characterization of the juice was carried out and values of 2.830 pH, 11.330 °Brix, 0.646% citric acid, 6290.411 μg Trolox⸱eq g⁻¹ of antioxidant activity, 20.284 mg⸱100g⁻¹ of vitamin C were obtained. , 11.114% total solids and 80.886% humidity. The factors evaluated for spray drying were inlet temperature (125 - 155°C), maltodextrin concentration (3 - 9%) and feed flow (3 - 6 mL⸱min⁻¹), which presented different degrees of significance on the response variables, which were color, moisture content, water activity, hygroscopicity, yield, antioxidant activity, vitamin C content, soluble solids, titratable acidity, pH and solubility. Using the Design-Expert program, it was found that the optimal combination to maximize yield (62.173%), antioxidant activity (6252.270 μg Trolox⸱eq g⁻¹) and vitamin C content (19.941 mg⸱100g⁻¹) was to apply 125 °C inlet temperature, 5.07% maltodextrin and 3 mL⸱min⁻¹ feed flow, values that were similar to those obtained in the laboratory (62.157% yield, 6251.572 μg Trolox⸱eq g⁻ ¹ antioxidant activity and 19,767 mg⸱100g⁻¹ vitamin C content) under the aforementioned conditions.